IgG4-Related Inflammatory Pseudotumor Involving the Clivus: A Case Report and Literature Review - Liu, Xiaohai; Wang, Renzhi; Li, Mingchu; Chen, Ge (Frontiers in Endocrinology, 2021)
IgG4-related inflammatory pseudotumor is very uncommon and characterized histologically by the presence of acute or chronic inflammatory pseudotumor with increasing IgG4-positive plasma cells and lymphocytes infiltrating the tissues. As reports of intracranial IgG4-related pseudotumors are very rare, here we reported a case of IgG4-related inflammatory pseudotumor involving the clivus mimicking meningioma. A 46-year-old male presented with intermittent headache for 2 years and a sudden onset dysphagia and dysphonia of 7 days’ duration alongside lower limbs weakness. Enhanced magnetic resonance imaging (MRI) of the skull base revealed an isointense signal on T1- and T2-weighted enhanced mass located at the middle of upper clivus region, for which a meningioma was highly suspected. The mass was partially resected via endoscopic transsphenoidal approach as the subdural extra-axial lesion was found to be very tough and firm, exhibiting fibrous scarring attaching to the brain stem, and pathological findings showed lots of IgG4-positive plasma cells and lymphocytes surrounded by rich collagen fibers. After the surgery, the patient achieved decompression of brain stem and posterior cranial nerves and improvement of the symptoms such as dysphagia, dysphonia and lower limbs weakness. And the patient was sent to rheumatology department for further glucocorticoids after the diagnosis of Ig IgG4-related inflammatory pseudotumor was made. This case highlights the importance of considering IgG4-related inflammatory pseudotumor as a differential diagnosis in patients with lesion involving clivus presenting with sudden onset symptoms of dysphagia and dysphonia alongside lower limbs weakness, when other more sinister causes have been excluded. IgG4-related inflammatory pseudotumor are etiologically enigmatic, confusing, and unpredictable, and total resection might not be warranted. Glucocorticoids are usually the first line of treatment after diagnosis